Profile, roles, and career development in the field of Library and Information Science from the different environment - Suja', Balqis (2004)
This is a three-hour forum filled by four speakers. The author talked on current scenario on cataloguing environment, computerized cataloguing, catalogue and cataloguing management, the future and challenge in providing cataloguing services and elements of self motivation in cataloguing.